Insecticidal Activity of Allium sativum Essential Oil-Based Nanoemulsion against Spodoptera littoralis - Giuliano, Gaetano; Campolo, Orlando; Forte, Giuseppe; Urbaneja, Alberto; Pérez-Hedo, Mertixell; Latella, Ilaria; Palmieri, Vincenzo; Giunti, Giulia (MDPI, 2024)
Spodoptera littoralis, commonly known as the Egyptian or African cotton leafworm, is a significant agricultural threat. It is widely distributed in Africa, Mediterranean Europe, and Middle Eastern countries. This polyphagous pest infests numerous crop plants across 44 families, including cotton, soybeans, alfalfa, sweet potato, pepper, eggplant, tomato, maize, lettuce, strawberry, wheat, and hibiscus. The damage caused by S. littoralis on different plant organs, such as young leaves, shoots, stalks, bolls, buds, and fruits, often determines substantial product losses. Current control strategies predominantly rely on synthetic insecticides, which, despite their efficacy, have notable drawbacks, including insecticide resistance, environmental contamination, consumer concerns, and adverse effects on non-target organisms and beneficial insects. In response to these challenges, in this study, we developed and evaluated a garlic EO-based nanoemulsion with a high EO concentration (15%) and low surfactant content to mitigate the possible negative impact on plants and to enhance efficacy against S. littoralis larvae. Laboratory bioassays demonstrated promising larvicidal activity and reduced larval feeding, although some phytotoxicity symptoms were observed. This study underscores the potential of botanical insecticides as sustainable alternatives to synthetic chemicals, emphasizing the importance of balancing efficacy with environmental and ecological considerations in pest management strategies.